Evaluating Students’ Academic Progress in the Role of Fuzzy Logic - Nabiel Algshat (AlQalam Journal of Medical and Applied Sciences, 2024)
This paper explores the role of fuzzy logic in the assessment of student performance in local high school, Badr, Libya, positing that it offers a more flexible and accurate alternative to traditional categorization methods of academic achievement. Conventional assessment tools, such as standardized test scores and GPAs, often yield a distorted and overly simplistic view of student performance. Utilizing a mixed-methods research design, this study compares the performance, attendance, and self-reported satisfaction of students assessed through fuzzy logic with those evaluated by traditional methods. The results demonstrate that students assessed using fuzzy logic achieved higher average scores and expressed greater satisfaction with the assessment process. Additionally, educators employing fuzzy logic provided more detailed and constructive feedback, enriching the learning experience. Thus, this research indicates that fuzzy logic can effectively mitigate the shortcomings of traditional assessment methods, enhancing the recognition of diverse student abilities. The findings advocate for the integration of fuzzy logic in educational assessment practices to promote inclusivity and improved learning outcomes. في هذه الورقة البحثية نستكشف دور المنطق الضبابي في تقييم أداء الطلاب في المدرسة الثانوية بمدينة بدر، ليبيا، حيث تفترض هذه الدراسة أن استخدام المنطق الضبابي وهو أحد أفرع الذكاء الاصطناعي، قد يوفر بديلاً أكثر مرونة ودقة لأساليب التقييم التقليدية لمستويات الطلاب العلمية. وغالبًا ما تؤدي أدوات التقييم التقليدية، مثل نتائج الاختبارات ونسب الدرجات، إلى تكوين صورة مبسطة وأحياناً غير عادلة لأداء الطلاب. فمن خلال استخدام تصميم بحثي يعتمد على عدة أساليب للتقييم، تم في هذه الدراسة المقارنة بين أداء الطلاب وحضورهم ورضاهم، حيث تم تقييمهم باستخدام المنطق الضبابي، مع أولئك الذين تم تقييمهم بطرق تقليدية. حيث أظهرت النتائج أن الطلاب الذين تم تقييمهم بواسطة المنطق الضبابي حققوا درجات متوسطة أعلى وأبدوا رضا أكبر عن عملية التقييم. بالإضافة إلى ذلك، قدم المعلمون الذين قاموا بتجربة المنطق الضبابي ملاحظات بناءً، مما أثرى تجربة التعلم بشكل كبير. وبالتالي، تشير هذه الدراسة إلى أن المنطق الضبابي يمكن أن يكون أداة فعالة لتخفيف العيوب المرتبطة بأساليب التقييم التقليدية، مما يعزز من القدرة على التعرف على التنوع في قدرات الطلاب العلمية. كما تؤيد النتائج المستخلصة من هذه الدراسة إلى أن دمج المنطق الضبابي مع ممارسات التقييم العلمي للطلاب، قد تساعد وبشكل كبير في تقييم نتائج طلاب المرحلة الثانوية وتحسين مخرجات التعلم